Recent Insurance And Takaful Coverage For Diabetics In Malaysia: A Review - Junaidah Abu Seman; Azrul Azlan Iskandar Mirza; Nurul Aini Muhamed; Zurina Kefeli@ Zulkefli; Mohd Radzniwan A Rashid; Aimi FadzirulKamarubahrin; Sharifah Fairuz Syed Muhamad; Saharuddin Ahmad (Society of Business and management, 2024)
Indexed by ERA